Gemblong and Kalang Obong Traditions on the 7th Day and After Death in Sendangdawuhan Village - Wafiq Alya Mustafida; Faizatul Ulya; Muhammad Helmy Kurniawan (FKIP, Universitas Palangka Raya, 2024)
The Indonesian nation consists of various religions, cultures, races, and tribes, or what can be called multicultural. In society, we are required to appreciate and respect the differences that exist in this country. The purpose of this paper is to discuss the Kalang Obong culture that can coexist with the Muslim community. In essence, Kalang Obong is held in a death ceremony. The conclusion of this research is that living in a nation and state that consists of various cultures, must have the awareness to respect and maintain the Kalang Obong Tradition. A tolerant attitude in religious moderation is needed by every citizen and community leader for the realization of peace.